Perbandingan Tingkat Kesembuhan Pasien Covid-19 Dengan Komorbid Diabetes Mellitus (DM) Berdasarkan Tingkat Usia Di Rumah Sakit Natar Medika Lampung Selatan - Firhat Esfandiari; Dita Fitriani; Toni Prasetya; Ade Sinta Purnama (Universitas Malahayati, 2022)
ABSTRACT Coronavirus Disease (COVID-19) is a highly contagious viral infection caused by Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2). This disease was first discovered in Wuhan, China, and has spread to 190 worldwide. On March 12, 2020, the World Health Organization (WHO) announced that COVID-19 is a global pandemic. COVID-19 can affect all ages, the elderly group with a history of comorbidities has a higher risk factor and has a higher risk of complications. The severity of COVID-19 is influenced by endurance, age, and several comorbid diseases, including asthma, diabetes mellitus, and hypertension. Especially for those with diabetes, it is the second most common comorbidity found, about 8% of cases, after hypertension, and with a mortality rate three times that of patients in general. This study aims to compare the recovery rate of COVID-19 patients with comorbid diabetes mellitus (DM) based on age level at Natar Medika Hospital, South Lampung in 2021. This study used an observational analytical method with a cross-sectional approach. The sample population used in patients who have confirmed COVID-19 with the Swab-PCR test and are hospitalized at the Natar Medika Hospital in South Lampung in 2021. The results of the Covid-19 study with comorbid DM at the pre-elderly age were obtained as many as 14 (82.4) patients recovered, and 3 patients died (17.6). Meanwhile, in the elderly, 20 (62.5) patients recovered and 12 (37.5) died. From the results of bivariate analysis using the Chi-Square method, a p-value of 0.202 (p>0.005) was obtained. There is no significant comparison between pre-elderly DM comorbid Covid patients with 19 elderly patients at Natar Medika Hospital, South Lampung, where p = 0.202 (p>0.005). Keywords: Healing Rate, COVID-19, Diabetes Mellitus, Age Level. ABSTRAK Coronavirus Disease (COVID-19) adalah infeksi virus yang mudah menular disebabkan oleh Severe Acute Respiratory Syndrom Coronavirus (SARS-CoV-2).Penyakit ini pertama kali ditemukan di Wuhan,China dan menyebar ke 190 di seluruh dunia. Pada 12 Maret 2020 World Health Organization (WHO) mengumumkan bahwa COVID-19 sebagai pandemik global.COVID-19 dapat menyerang segala kalangan usia, kelompok usia lanjut dengan riwayat komorbid memiliki faktor resiko lebih tinggi dan memiliki risiko lebih tinggi terjadinya komplikasi%).Tingkat keparahan COVID-19 dipengaruhi oleh daya tahan tubuh, usia, dan beberapa penyakit komorbid, diantaranya adalah asma, diabetes melitus, dan hipertensi. Khusus untuk mereka dengan diabetes, merupakan komorbiditas kedua tersering ditemukan, sekitar 8% kasus, setelah hipertensi , dan dengan angka kematian tiga kali lipat dibandingkan penderita secara umum. Penelitian ini bertujuan untuk mengetahui perbandingan tingkat kesembuhan pasien covid-19 dengan komorbid diabetes mellitus (DM) berdasarkan tingkat usia di rumah sakit Natar Medika lampung selatan tahun 2021. Penelitian ini menggunakan metode Analitik observasional dengan pendekatan cross sectional. Dengan populasi sampel yang digunakan yaitu pasien yang terkonfirmasi COVID-19 dengan test Swab-PCR dan di rawat inap di Rumah Sakit Natar Medika lampung selatan tahun 2021. Covid-19 dengan komorbid DM pada usia Pra Lansia didapatkan sebanyak 14 (82,4) pasien Sembuh, dan pasien Meninggal sebanyak 3 (17,6). Sedangkan pada usia Lansia sebanyak 20 (62,5) pasien sembuh dan pasien Meninggal sebanyak 12 (37,5)..Dari hasil analisis bivariat dengan menggunakan metode Chi-Square didapatkan p-value sebesar 0,202 (p>0,005). Tidak Terdapat perbandingan yang signifikan antara pasien Covid komorbid DM pada pra lansia dengan pasien lansisa 19 di Rumah Sakit Natar Medika lampung selatan. Kata Kunci : Tingkat Kesembuhan, COVID-19, Diabetes Melitus, Tingkat Usia